Peptide binding at the GLP-1 receptor. (20th July 2007) - Mann, R.; Nasr, N.; Hadden, D.; Sinfield, J.; Abidi, F.; Al-Sabah, S.; de Maturana, R. López; Treece-Birch, J.; Willshaw, A.; Donnelly, D.
Abstract : The receptor for GLP-1 [glucagon-like peptide-1-(7–36)-amide] is a member of the 'Family B' of GPCRs (G-protein-coupled receptors) comprising an extracellular N-terminal domain containing six conserved cysteine residues (the N-domain) and a core domain (or J-domain) comprising the seven transmembrane helices and interconnecting loop regions. According to the two-domain model for peptide binding, the N-domain is primarily responsible for providing most of the peptide binding energy, whereas the core domain is responsible for binding the N-terminal region of the peptide agonists and transmitting the signal to the intracellular G-protein. Two interesting differences between the binding properties of two GLP-1 receptor agonists, GLP-1 and EX-4 (exendin-4), can be observed. First, while GLP-1 requires its full length to maintain high affinity, the eight N-terminal residues of EX-4 can be removed with little reduction in affinity. Secondly, EX-4 (but not GLP-1) can bind to the fully isolated N-domain of the receptor with an affinity matching that of the full-length receptor. In order to better understand these differences, we have studied the interaction between combinations of full-length or truncated ligands with full-length or truncated receptors.